Is Higher BMI Associated with Worse Overall Mortality in Hepatocellular Carcinoma Patients? An Evidence Based Case Report - Alessa Fahira; Ratu Shafira Hanifah; Mohamad Prasetio Wardoyo; Amirah Deandra Diba; Rahadian Ramadhan; Julie Dewi Barliana; Chyntia Olivia Jasirwan (Acta Medica Indonesiana, 2020)
Background: liver cancer is currently the second deadliest cancer in the world with hepatocelullar carcinoma (HCC) being the commonest form—accounting 90% of all its cases. With the current global alarming increase of obesity, there is hence an increase of fatty liver disease cases, which is one of the major non-viral etiology of cirrhosis in the world. The objective of this study is to evaluate whether obese HCC patients have worse survival outcome. Methods: PubMed, Cochrane, Scopus, ProQuest, and EBSCOhost were comprehensively searched for systematic review and cohort prognostic researches studying overall survival of HCC patients who are underweight and obesity according to their BMI. Three studies were selected and critically appraised. Data were then summarized descriptively. Results: the three studies included consist of one meta-analysis and two cohort studies. Meta-analysis study stated no association between overweight and obesity status with higher mortality rate in Asian race HCC patients (aHR, 1.10; 95% CI, 0.63-1.92). A cohort study from Japan reported while there was a significant difference of mortality rate in obese HCC patients in bivariate analysis, adjustment with other important prognostic factors with multivariate analysis found no significant correlation between obesity and HCC-related mortality rate (aHR, 1.00; 95% CI, 0.83-1.22). Another cohort study from China reported that HCC-related mortality rate in patients with higher BMI was lower than in patients with lower BMI (aHR, 0.347; 95% CI, 0.239-0.302). Conclusion: there is no association between higher BMI with HCC-related mortality in Asian race patients.